Analisis Pengaruh Content Marketing, Influencer dan Sosial Media Terhadap Keputusan Pembelian Konsumen Pada Pengguna Instagram di Universitas Mataram - Ardina, Gusti Ayu Dwi Novia; Dwi Putra Buana Sakti, Dwi Putra Buana Sakti; Lalu Edy Herman Mulyono, Lalu Edy Herman Mulyono (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to analyze the influence of content marketing, influencers, and social media on consumer purchasing decisions for Instagram users at Mataram University. The population in this study were Instagram application users in the Mataram University area, while the sample from this study was 100 Instagram application users using purposive sampling techniques. This type of research is associative research. Data processing in this study used SPSS 26.0 for Windows, where validity tests, reliability tests, classical assumption tests, causal step regression tests, significance tests (t tests) and coefficient of determination tests (R2) were carried out. Based on the research results, it shows that: Content marketing has a positive and significant influence on purchasing decisions for Instagram users at Mataram University, influencers have a positive and significant influence on purchasing decisions for Instagram users at Mataram University, and social media has a positive and significant influence on purchasing decisions. to Instagram users at Mataram University. The results of testing the coefficient of determination (R2) show that the adjusted R Square value is 0.433 (43.3%). This value shows that the influence of content marketing, influencers, and social media on consumer purchasing decisions for Instagram users at Mataram University is 43.3%, the remaining 56.7% is explained by other variables outside the research.